Sperm chromatin: evaluation, epigenetic signatures and relevance for embryo development and assisted reproductive technology outcomes - Balder, P; Jones, C; Coward, K; Yeste, M (Elsevier, 2024)
Sperm chromatin is distinct from somatic cell chromatin, as a result of extensive remodeling during the final stages of spermatogenesis. In this process, the majority of histones is replaced with protamines. The chromatin is consequently highly condensed and inert, which facilitates protection of the DNA. The sperm epigenomic landscape is shaped by histone retention, histone and protamine modification, DNA methylation, and RNAs. In recent years, sperm chromatin integrity and its epigenetic marks have been increasingly studied, and the constitution of sperm chromatin is steadily being uncovered. This growing body of research prompts assessment of the frequently overlooked involvement of sperm in fertility and embryonic development. Moreover, numerous endogenous and exogenous factors are known to affect sperm chromatin, which may in turn impact the reproductive success. Concerns have been raised about the effects of assisted reproductive technology (ART) on the sperm epigenome, embryonic development and offspring health. This review examines the structure and epigenetic signatures of sperm chromatin in the context of fertility and early embryonic development. Additionally, sperm chromatin evaluation and causes of aberrant integrity are outlined. Building on the knowledge discussed in the current review, future research should aim to elucidate the intricate relationship between all aspects of sperm chromatin and embryo development. This could lead to the uncovering of new targets for treating infertility, as well as the acquisition of much needed insights into the possible reciprocal association between ART and sperm chromatin integrity.